Effects of thriving at work on employees’ family role performance: A moderated mediation model - Yang, Baoyan; Su, Shaoqing; Zong, Zhaobiao; Du, Qiaoqiao; Wang, Junyi (Frontiers in Psychology, 2023)
Objective Existing research has demonstrated that thriving at work has a positive effect on work performance, but little is known about how thriving at work affects family role performance. Based on the work–home resource model, this study examines the impact mechanism of thriving at work on family role performance. Methods This paper uses an experience sampling method to conduct a 5-day daily study of 151 married employees in Northwest China, and the data were analyzed using a multilevel linear model. Results We find that thriving at work positively affects family role performance partly through the mediating effect of work–family enrichment at the individual level. Moreover, family-supportive supervisor behavior moderates the relationship between thriving at work and work–family enrichment. Through work–family enrichment, family-supportive supervisor behavior also moderates the indirect relationship between thriving at work and family role performance. Specifically, the higher the level of family-supportive supervisor behavior, the stronger the indirect effect of thriving at work on family role performance through work–family enrichment. Conclusion Previous research has focused more on the effects of thriving at work within the work domain, suggesting that thriving at work can have a positive impact on work outcomes. However, only a few studies have examined the positive relationship between thriving at work and family role performance from the perspective of employees’ positive psychological resources. This paper explores the positive effects of thriving at work on family role performance based on a resource flow perspective and identifies its potential boundary conditions. This study enriches the theoretical research on the relationship between thriving at work and family role performance. Additionally, it provides a new foothold and research perspective on improving work–family enrichment.